Comparison of two different toxin-induced kidney fibrosis models in terms of inflammatory responses. (November 2021) - Yang, Yejin; Ha, Sugyeong; Jeong, Somi; Jang, Chae Won; Kim, Jeongwon; Im, Dong-Soon; Chung, Hae Young; Chung, Ki Wung
Abstract: Chronic kidney disease (CKD) is characterized by persistent abnormalities in kidney function, accompanied by structural changes. Interstitial fibrosis, characterized by the accumulation of extracellular matrix (ECM) proteins, is frequently detected during CKD development. Given the multiple underlying causes of CKD, numerous animal models have been developed to advance our understanding of human nephropathy. Herein, we compared two reliable toxin-induced mouse kidney fibrosis models in terms of fibrosis and inflammation. Administration of folic acid (250 mg/kg, intraperitoneal injection) or an adenine diet (0.25 % for three weeks) afforded similar effects on kidney function, as detected by increased serum nitrogen levels. In addition, the kidneys exhibited a similar extent of tubule dilation and kidney damage. The degree of fibrosis was compared using various biological methods. Although both models developed a significant fibrotic phenotype, the adenine diet-fed model showed a marginally higher increase in fibrosis than the folic acid model, as reflected by increased kidney ECM gene and protein levels. We further compared inflammatory responses in the kidneys. Interestingly, pro-inflammatory responses, including cytokine expression and immune cell infiltration, were significantly increased in adenine diet-fed kidneys. Furthermore, collagen expression was identified in the macrophage-infiltrated region, implying the importance of inflammation in fibrogenesis. Collectively, we observed that the adenine diet-fed kidney fibrosis model presented a higher inflammatory response with increased fibrosis when compared with the folic acid-induced kidney fibrosis model, indicating the importance of the inflammatory response in fibrosis development.